Analisis Kendala Internal Mahasiswa dalam Menulis Karya Ilmiah - Rahmiati, Rahmiati (Al-Daulah : Journal of Criminal Law and State Administration Law, 2014)
This paper presents research on the analysis of internal hinderances students encounter in writing academic papers in higher education context. The aim is to canvass university student’s espoused conceptions of the internal hinderances and solutions regarding their difficulties in writing academic works. Data were generated from individual interviews and focus group discussions with 56 university  learners. Data were analyzed using inductive  and  deductive approaches. The findings indicate several key  findings  related  to  what  internal hinderaces students face in producing academic writing. Among the internal hinderances are issues related to laziness to write, lack of mood in writing, difficulties in findings topics or ideas to write, lack of self confidence in writing, and difficulties to start writing. This paper also reveals several strategic  internal solutions to overcome those internal hinderance  which include building internal motivation to write, changing thinking paradigm related to writing, and being creative in writing. Keywords: Writing, Academic Papers, Difficulties